Pelatihan Pertolongan Pertama Dan Cidera Olahraga Di Sekolah Menengah Kejuruan Negeri 5 Bengkulu Selatan - Sumantri, Ajis; Putra, Dwinky Marta; Ertanto, Dodi; Lismana, Oetari (Jurnal Dehasen Untuk Negeri, 2024)
The report on first aid and sports injury training at State Vocational High School 5 Bengkulu Selatan in 2024 describes efforts to enhance awareness and skills in handling sports injuries among students. This training highlights the importance of prompt response and proper handling when dealing with minor or serious injuries during sports activities. Participants are trained to identify signs of injury, provide effective first aid, and manage emergency situations calmly and systematically. Additionally, the training also provides understanding of preventive measures for sports injuries. It is hoped that with the improvement of these skills and knowledge, the school can create a safer and supportive environment for students to engage in sports activities.